Design of interactive learning courseware for data structures - Farn, Choy Ying (Nanyang Technological University, 2020)
Online E-learning has been stepping ahead and increasing popularity in educations where every educational is acquired basic skills in Information Technology in academics. It has shown great progressiveness for students and teachers for delivering and managing the courses in the modern period for learning environments pace. To understand globally has transformed its academic information content from traditional physical books to electronics books without needs for the student to physically attending the academic setting. Education hold with the pace of development for technology and many platforms are available to guidance on designing and developing good courseware. Upon building into this final year project of developing a learning environment through the learning platforms, one of the learning management systems would be named Moodle, as Moodle obtains the best popularity recognition globally across the world. Moodle’s documentation and guiding on its ability has been constantly upgrading and greatly implementation. Moodle great benefit is an open-source platform that can immediately develop the courseware by downloading the packages for free for available users. Moodle has many customization functions and ready features for users to start design and develop their courseware. Therefore, this overall of this project focuses and designs mainly on the component that Moodle provides to support courseware that serves delightsome for study activities and gamification features to enhance student's experience